Allosteric Tuning of Caspase‐7: A Fragment‐Based Drug Discovery Approach - Vance, Nicholas R. (Angew Chem Int Ed Engl, 2017)
The caspase family of cysteine proteases are highly sought‐after drug targets owing to their essential roles in apoptosis, proliferation, and inflammation pathways. High‐throughput screening efforts to discover inhibitors have gained little traction. Fragment‐based screening has emerged as a powerful approach for the discovery of innovative drug leads. This method has become a central facet of drug discovery campaigns in the pharmaceutical industry and academia. A fragment‐based drug discovery campaign against human caspase‐7 resulted in the discovery of a novel series of allosteric inhibitors. An X‐ray crystal structure of caspase‐7 bound to a fragment hit and a thorough kinetic characterization of a zymogenic form of the enzyme were used to investigate the allosteric mechanism of inhibition. This work further advances our understanding of the mechanisms of allosteric control of this class of pharmaceutically relevant enzymes, and provides a new path forward for drug discovery efforts.